2020
DOI: 10.3389/fcimb.2020.00110
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Affect ROS Production and Fibroblast Migration in an In-vitro Model of Sinonasal Wound Healing

Abstract: Introduction: Antibiotics are often administered to patients perioperatively and have been shown to affect ROS production of nasal cells in vitro, but their effect in the setting of active wound healing remains unclear. Reactive oxygen species (ROS) are known to play a significant role in wound healing. This study analyzed a broad array of antibiotics used after sinus surgery to assess their effect on wound healing and ROS production in vitro. It was hypothesized that ROS production would be affected by these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
14
0
2
Order By: Relevance
“…Furthermore, we first unveiled the inhibitory effect of MitoQ on LF activation. Similarly, studies also demonstrated MitoQ can prevent the activation of cardiac and nasal fibroblast [ 29 , 30 ]. In addition, the antifibrotic effect of MitoQ has been evidenced in lung [ 3 ], liver [ 31 ] and kidney [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we first unveiled the inhibitory effect of MitoQ on LF activation. Similarly, studies also demonstrated MitoQ can prevent the activation of cardiac and nasal fibroblast [ 29 , 30 ]. In addition, the antifibrotic effect of MitoQ has been evidenced in lung [ 3 ], liver [ 31 ] and kidney [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may result from the complex redox homeostasis mechanisms [36,58]. ROS promote fibroblast proliferation, myofibroblasts differentiation, EMT, and collagen deposition [59][60][61]. The glycolysis might be an adaptive shift to avoid the oxidative stress caused by OXPHOS [36].…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 leads also to the production of reactive oxygen species (ROS) in AE cells and ROS derived from DUOX2 leads to increased IL-8 secretion [ 127 ]. Interestingly, elevated levels of ROS in the freshly wounded nasal epithelial cells and fibroblasts obtained from CRS individuals might be reduced by some antibiotics and trigger a decline in nasal fibroblast migratory capacity without affecting nasal epithelial cells [ 128 ]. Recently, studies demonstrated the role of HMGB1-RAGE signaling pathway in the process of epithelial to mesenchymal transition (EMT) in the case of CRSwNP patients.…”
Section: Other Selected Aspects Of Crs Pathogenesismentioning
confidence: 99%